2022
DOI: 10.3389/fsurg.2022.991704
|View full text |Cite
|
Sign up to set email alerts
|

Robotic multiquadrant colorectal procedures: A single-center experience and a systematic review of the literature

Abstract: PurposeRobotic surgery has been progressively implemented for colorectal procedures but is still limited for multiquadrant abdominal resections. The present study aims to describe our experience in robotic multiquadrant colorectal surgeries and provide a systematic review and meta-analysis of the literature investigating the outcomes of robotic total proctocolectomy (TPC), total colectomy (TC), subtotal colectomy (STC), or completion proctectomy (CP) compared to laparoscopy.MethodsAt our institution 16 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(158 reference statements)
0
9
0
Order By: Relevance
“…Although not statistically relevant, we observed no conversions in our limited robotic cohort. A 2018 systematic review reported a conversion rate of 7.3%, while a more recent one from 2022 reported conversion rates of 1.7% and 3.4% for total/subtotal colectomy and total proctocolectomy/completion colectomy, respectively [28], [29]. In 2021, Flynn et al observed similar learning curves for robotic and laparoscopic surgery as well as lower conversion rates, especially during the early phases of learning [30].…”
Section: Resultsmentioning
confidence: 99%
“…Although not statistically relevant, we observed no conversions in our limited robotic cohort. A 2018 systematic review reported a conversion rate of 7.3%, while a more recent one from 2022 reported conversion rates of 1.7% and 3.4% for total/subtotal colectomy and total proctocolectomy/completion colectomy, respectively [28], [29]. In 2021, Flynn et al observed similar learning curves for robotic and laparoscopic surgery as well as lower conversion rates, especially during the early phases of learning [30].…”
Section: Resultsmentioning
confidence: 99%
“…The choice between laparoscopic and robotic IPAA currently seems to depend mostly on the surgeon’s preference, platform availability, and type of practice, given the high costs of the robot and the lack of evidence on its superiority compared to laparoscopy. As with other procedures that require multiquadrant exposure, TPC can also be performed with a combination of laparoscopy and robotics, 66 maximizing the advantages of the 2 approaches. Particular attention should be paid to technical minutiae, such as the extent of pelvic dissection and correct mesentery alignment, when performing MI-IPAA.…”
Section: Open Versus Mi-ipaamentioning
confidence: 99%
“…Twenty-three reviews on colectomy were included [30,31,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Of the twentythree reviews, two were systematic reviews [30,57], eighteen were meta-analyses [31,37,39,40,[42][43][44][45][46][47][49][50][51][52][53]55,56,58], and three were network meta-analyses [41,48,54]. The corrected covered area of the 23 reviews was 2.6% (slight overlap).…”
Section: Colectomymentioning
confidence: 99%